A numerical homogenization study of the elastic property of a soil-rock mixture using random mesostructure generation. (June 2018) - Meng, Q.X.; Wang, H.L.; Xu, W.Y.; Cai, M.
Abstract: A random generation method of periodic mesostructures of soil-rock mixtures based on random polygon is proposed and used in the generation of an RVE model. A code for generating a periodic mesh and periodic boundary is developed for the numerical simulation. Macroscopic elastic parameters of the SRMs are calculated based on the simulation using numerical homogenization. The elastic modulus shows a size effect, namely, the modulus deceases gradually with an increase in the model size. The border effect is related to the model size and is large in small-sized models. Rock aggregates arranged in a certain direction induce property anisotropy.